Keeping the Tensions: The Path to an Open, Inviting, Communicative, and Responsible Practice of Baptism in a Secular Society - Landová, Tabita (International journal of practical theology, 2024)
The study deals with the difficulties and challenges being faced by the practice of baptism in contemporary secular society. Based on empirical research on the practice of the Evangelical Church of Czech Brethren, the author argues for an open, inviting, communicative, and responsible practice of baptism that does not erase present tensions but deals with them creatively and situationally. The Church should take seriously the basic inclusive impulse of the Gospel while being aware of its baptismal responsibility, which consists primarily in the subsequent pastoral care of the baptised. The results of the study may inspire those who are involved in the pastoral ministry in similar contexts.